2019
DOI: 10.1002/bab.1803
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and antibiotic activity of silver nanoparticles using different sources: Glass industrial sewage‐adapted Bacillus sp. and herbaceous Amaranthus sp

Abstract: Synergistic effects of metallic nanoparticles (NPs) with commonly used antibiotics have encouraged the exploration of novel biological entities, including bacteria and weed plants. The present study for the first time reports the capability of an extracellular fraction of Bacillus sp. isolated from effluents of a glass‐manufacturing unit to biosynthesis silver nanoparticles (AgNPs) without hazardous materials. Besides, the biosynthesis of AgNPs using an aqueous extract of herbaceous weed plant (Amaranthus sp.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(50 reference statements)
2
4
0
Order By: Relevance
“…This result was higher than that obtained from the TEM analysis. Similar results were also obtained in previous studies reported by Bahrami‐Teimoori et al 20 . and Bharathi et al.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result was higher than that obtained from the TEM analysis. Similar results were also obtained in previous studies reported by Bahrami‐Teimoori et al 20 . and Bharathi et al.…”
Section: Resultssupporting
confidence: 92%
“…This result was higher than that obtained from the TEM analysis. Similar results were also obtained in previous studies reported by Bahrami-Teimoori et al 20 and Bharathi et al for biosynthesized AgNPs. 59 According to the literature, this size difference that was observed between the results is probably related to the fact that the size of NPs in dried form is evaluated by TEM, whereas the DLS analysis measures the hydrodynamic radius of particles, which can result in an overestimation of particle size.…”
Section: Transmission Electron Microscopy (Tem)supporting
confidence: 92%
See 1 more Smart Citation
“…Srivastava and Mukhopadhyay ( 2013 ) described selenium nanostructures’ biosynthesis from selenium oxyanions by using the bacteria Zooglea ramigera . Bahrami-Teimoori et al ( 2019 ) has demonstrated that both natural sources; industrial wastewater-acclimated Bacillus sp. and wild-growing Amaranthus sp.…”
Section: Circular Bioresource Utilization For the Synthesis Of Nanopa...mentioning
confidence: 99%
“…27 Currently, lipopeptide-mediated nanomaterial synthesis has been used as an alternative material for implementation in research as antibiotic agents. 31,32 The effects of green nanoparticles have shown influence in bactericidal against Grampositive/negative bacteria and, fungal pathogens and gene therapy applications, 33 however, most of the researchers have recommended the use of Gram-positive bacteria to produce the lipopeptides biosurfactants. 34 Additionally, low toxicity and more biodegradability of lipopeptide biosurfactant-mediated nanomaterial synthesis have established eco-friendly materials with core effectiveness in the research and development sector.…”
Section: Introductionmentioning
confidence: 99%